Given,
The center of the circle is (6, -3).
The coordinates of the point, circle is passing through (6,6).
The general equation of the circle is,
![(x-h)^2+(y-k)^2=r^2](https://img.qammunity.org/2023/formulas/mathematics/college/5s77z5lwu6jnvb5vkwanu2jvhq5sh1qkc3.png)
Here, x, y are the coordinates of the point.
h and k are the center of the circle.
r is the radius of the circle.
Substituting the value of h, k , x and y in the equation of circle then,
![\begin{gathered} (6-6)^2+(6-(-3))^2=r^2 \\ 0+9^2=r^2 \\ r=9 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/68i2gu5xka6qx7i2bk7kyh1mn69haeypw4.png)
So, the radius of the circle is 9.
Substituting the value of h, k and r in the general equation of circle.
![\begin{gathered} (x-6)^2+(y-(-3))^2=9^2 \\ x^2+36-12x+y^2+9+6y=81 \\ x^2+y^2-12x+6y-36=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/6hmjo0sm5iqe7byvap1lnju6ib4nnjtvs8.png)
Hence, the equation of circle is x^2+y^2-12x+6y-36=0